Organoleptic Quality of Dodol Made from Palm Fruit (Borrasus flabellifer) - I Gede Relung Swastyayana; Ni Putu Eka Trisdayanti; I Made Rumadana; Hardina (PT FORMOSA CENDEKIA GLOBAL, 2025)
Lontar fruit is a fruit that comes from the Lontar tree or also known as Palmyra. This study aims to determine the quality and describe the final results of processing lontar fruit as a basic ingredient in making dodol. Dodol is a traditional food that has a sweet taste and chewy texture. The data collection method used in this study was an experiment which was then continued with documentation, organoleptic tests were analyzed using a Likert scale to get the best results from dodol made from Lontar fruit. The test results from 20 fairly trained panelists who were students of the culinary arts study program at the Bali Tourism Polytechnic. The conclusion of this study is that dodol made from lontar fruit gets an average rating of 90%, namely with very good interpretation criteria.